2017
DOI: 10.1371/journal.pone.0170751
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Proprioceptive Sensory Innervation of the Mouse Soleus: A Whole-Mount Muscle Approach

Abstract: Muscle proprioceptive afferents provide feedback critical for successful execution of motor tasks via specialized mechanoreceptors housed within skeletal muscles: muscle spindles, supplied by group Ia and group II afferents, and Golgi tendon organs, supplied by group Ib afferents. The morphology of these proprioceptors and their associated afferents has been studied extensively in the cat soleus, and to a lesser degree, in the rat; however, quantitative analyses of proprioceptive innervation in the mouse soleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 39 publications
4
23
0
Order By: Relevance
“…Second, we showed that the cell bodies of Nxph1 + neurons are smaller than the average PV + neuron cell body size (mean cell body diameter 24.5 ± 0.4 μm for Nxph1 , n= 88 neurons; 27.6 ± 0.4 μm for PV , n= 183 neurons; p<0.001, Student’s t-test), consistent with the notion that type II afferent neurons are smaller in caliber than groups Ia or Ib neurons, (Matthews, 1972; Wu et al, 2019). Third, based on morphological observations that MS are typically innervated by one group Ia and one to two group II afferents, the ratio of cluster 1 (group Ia) to cluster 2-4 (putative group IIs) we observed (1:1.53) aligns with the expected ratio for group Ia:group II afferents (1:1.5) (Banks et al, 1982; data not shown; but see Sonner et al, 2017). To test if class 2-4 neurons represent group II afferents, we examined the expression of the class 4 marker Tachykinin 1 ( Tac1 ) in DRG and muscle.…”
Section: Resultssupporting
confidence: 79%
“…Second, we showed that the cell bodies of Nxph1 + neurons are smaller than the average PV + neuron cell body size (mean cell body diameter 24.5 ± 0.4 μm for Nxph1 , n= 88 neurons; 27.6 ± 0.4 μm for PV , n= 183 neurons; p<0.001, Student’s t-test), consistent with the notion that type II afferent neurons are smaller in caliber than groups Ia or Ib neurons, (Matthews, 1972; Wu et al, 2019). Third, based on morphological observations that MS are typically innervated by one group Ia and one to two group II afferents, the ratio of cluster 1 (group Ia) to cluster 2-4 (putative group IIs) we observed (1:1.53) aligns with the expected ratio for group Ia:group II afferents (1:1.5) (Banks et al, 1982; data not shown; but see Sonner et al, 2017). To test if class 2-4 neurons represent group II afferents, we examined the expression of the class 4 marker Tachykinin 1 ( Tac1 ) in DRG and muscle.…”
Section: Resultssupporting
confidence: 79%
“…2013; Sonner et al . 2017). To analyse the number of spindles per muscle, entire soleus muscles were cryosectioned and each section was stained with anti‐vGluT1 antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…1989; Sonner et al . 2017). Type II afferents have so far not been detected in mice by immunohistochemical and electrophysiological methods (Wilkinson et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Sonner et al . ). Afferent neurons generate action potentials with frequencies that are proportional to the size of the stretch and to the rate of stretching (De‐Doncker et al .…”
Section: Introductionmentioning
confidence: 97%
“…The central (equatorial) part of intrafusal muscle fibres is innervated by two types of afferent proprioceptive sensory neurons (termed 'type Ia afferents' and 'type II afferents' according to their axonal conduction velocity; Banks, 2015). Type Ia afferents form so called annulospiral sensory nerve endings whereas type II afferents flank the Ia afferents (Schroder et al 1989;Sonner et al 2017). Afferent neurons generate action potentials with frequencies that are proportional to the size of the stretch and to the rate of stretching (De-Doncker et al 2003).…”
Section: Introductionmentioning
confidence: 99%